The Gap Between Islamic Inheritance Law and Community Practice: A Legal Sociological Analysis of Inheritance Distribution in Indonesian Society - Rahmad Hidayad (Jurnal Indonesia Sosial Sains, 2026)
Islamic inheritance law has a strong normative foundation and regulates inheritance distribution in detail to achieve justice and legal certainty. However, in Indonesian social practice, its implementation often deviates from normative provisions due to legal system plurality and socio-cultural factors. This research aims to analyze the gap between Islamic inheritance law norms (das sollen) and inheritance distribution practices in society (das sein), as well as identify the influencing factors. The research employs an empirical juridical approach with data collection techniques through interviews with community members and religious leaders in Bukik Sikumpa, Lareh Sago Halaban District, Lima Puluh Kota Regency, West Sumatra. The results of the study show that the practice of inheritance distribution tends to be based on family deliberation, local customs, and consideration of the economic condition of the heirs, so that they do not fully follow the provisions of faraidh. The construction of the thought of community leaders also shows that Islamic inheritance law serves more as a normative reference than a binding primary guideline. From a legal sociology perspective, this phenomenon is influenced by the dominance of legal culture, the applicability of customary law as living law, and the low internalization of Islamic inheritance law in society. Social harmonization and conflict avoidance further reinforce the tendency to deviate from legal norms. Therefore, the effectiveness of Islamic inheritance law depends on the alignment between legal norms and living social values. This research emphasizes the need for an integrative approach between Islamic law and social reality to achieve inheritance law harmonization in Indonesia.